Centralized and Distributed Reconfigurable Intelligent Surfaces Assisted NOMA - Kumar M.H.; Sharma S.; Deka K.; Thottappan M. (My University, 2025)
Reconfigurable intelligent surfaces (RIS) and non-orthogonal multiple access (NOMA) are promising technologies for next-generation wireless networks. RIS can reconfigure wire-less channels through passive reflecting elements, and NOMA enhances spectral efficiency (SE) and connectivity. In this paper, a base station (BS) transmits superimposed precoded symbols to near and far users via two different RIS deployment strategies. Initially, a single RIS is deployed at the BS and consists of N passive reflecting elements, referred to as centralized deployment of RIS-assisted NOMA (CDR-NOMA). On the other hand, two RISs having N/2 elements are kept at users and referred to as distributed deployment of RIS-assisted NOMA (DDR-NOMA). We have optimized the phase shift at RIS using the semidefinite relaxation (SDR) technique to maximize the received signal-to-noise ratio (SNR). Simulation results show that the bit error rate (BER) of the CDR-NOMA system is superior to the DDR-NOMA and a conventional RIS-assisted NOMA system. Further, the sum-rate of the proposed CDR-NOMA and DDR-NOMA is calculated and it is better than the orthogonal multiple access (OMA). Furthermore, impact of transmitting antennas and reflecting surfaces are studied on the sum-rate and BER performance in the CDR-NOMA and DDR-NOMA. © 2022 IEEE.